Testosterone induces sexual dimorphism during infection with Plasmodium berghei ANKA - Aguilar-Castro, Jesús; Cervantes-Candelas, Luis Antonio; Buendía-González, Fidel Orlando; Fernández-Rivera, Omar; Nolasco-Pérez, Teresita de Jesús; López-Padilla, Monserrat Sofía; Chavira-Ramírez, David Roberto; Cervantes-Sandoval, Armando; Legorreta-Herrera, Martha (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria is the most lethal parasitic disease worldwide; men exhibit higher mortality and more severe symptomatology than women; however, in most studies of immune response in malaria, sex is not considered a variable. Sex hormones 17β-oestradiol and testosterone are responsible for the main physiological differences between sexes. When interacting with their receptors on different immune cells, they modify the expression of genes that modulate cell proliferation, differentiation, and synthesis of cytokines. The immunosuppressive activity of testosterone is well accepted; however, its participation in the sexual dimorphism of the immune response to malaria has not been studied. In this work, we analysed whether altering the concentration of testosterone, through increasing the concentration of this hormone for exogenous administration for three weeks, or gonadectomy before infection with Plasmodium berghei ANKA affects different cells of the immune response necessary for parasite clearance. We also assessed the concentration of pro-and anti-inflammatory cytokines in male and female CBA/Ca mice infected or not with the parasite. Our results show that testosterone changes affect females more than males, resulting in sex-associated patterns. Testosterone administration increased parasitaemia in intact males while reducing it in intact females leading to a dimorphic pattern. In addition, gonadectomy increased parasitaemia in both sexes. Moreover, testosterone administration prevented both weight loss caused by the infection in females and hypothermia in gonadectomized mice of both sexes. Boosting testosterone concentration increased CD3+ and CD8+ populations but decreased the B220+ cells exclusively in females. Additionally, testosterone reduced IFN-γ concentration and increased IL-6 levels only in females, while in males, testosterone increased the number of NK cells. Finally, gonadectomy decreased TNF-α concentration in both sexes. Our results demonstrate that testosterone induces different patterns depending on sex and testosterone concentration. Our findings explain, at least in part, the involvement of testosterone in the sexual dimorphism of the immune response to malaria and suggest possible implications for the efficacy of sex-differential drug therapies and vaccines.